2017
DOI: 10.1186/s40479-017-0069-1
|View full text |Cite
|
Sign up to set email alerts
|

Family Connections versus optimised treatment-as-usual for family members of individuals with borderline personality disorder: non-randomised controlled study

Abstract: BackgroundBorderline personality disorder (BPD) is challenging for family members who are often required to fulfil multiple roles such as those of advocate, caregiver, coach and guardian. To date, two uncontrolled studies by the treatment developers suggest that Family Connections (FC) is an effective programme to support, educate and teach skills to family members of individuals with BPD. However, such studies have been limited by lack of comparison to other treatment approaches. This study aimed to compare t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
71
0
16

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(95 citation statements)
references
References 17 publications
8
71
0
16
Order By: Relevance
“…A total of 11 studies describing seven interventions for or involving carers of people with BPD were retained. Six studies were conducted in the USA, two in Australia, one in the Republic of Ireland and two in the UK . Table provides a brief description of each intervention and identifies the associated studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 11 studies describing seven interventions for or involving carers of people with BPD were retained. Six studies were conducted in the USA, two in Australia, one in the Republic of Ireland and two in the UK . Table provides a brief description of each intervention and identifies the associated studies.…”
Section: Resultsmentioning
confidence: 99%
“…Three of the seven interventions are based on DBT principles, with the others based on cognitive behavioural therapy and transactional analysis, cognitive analytic therapy, mentalization‐based therapy (MBT) and relational models . All interventions were structured as multi‐family group sessions, and none described any additional tailoring to meet individual needs of group members.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these findings are encouraging, it should be observed that the optimized treatment as usual consisted of 3 didactic group sessions of psychoeducation in which information about BPD and the DBT model were provided. Thus, it did not constitute a direct comparison group to the FC intervention due to the significant variation in duration between the programs [47]. Moreover, Cohen d values for treatment effect (FC vs. optimized treatment as usual) ranged from 0.31 (depression) to 0.58 (grief), being in the small-to-moderate range.…”
Section: Family Interventions Designed To Address the Problems Of Thementioning
confidence: 99%
“…Recently, Flynn et al [47] carried out a nonrandomized controlled study on the effectiveness of FC ( n = 51) as compared to an optimized treatment-as-usual program ( n = 29) in a sample of 80 family members. The FC program showed significantly larger reductions from pre- to postintervention assessments for burden and grief.…”
Section: Family Interventions Designed To Address the Problems Of Thementioning
confidence: 99%